1998
DOI: 10.1143/jjap.37.l743
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Driving Voltage of In-Plane Switching Liquid Crystal Displays Using Photo-Alignment Method

Abstract: In-plane switching liquid crystal displays (IPS-LCDs) have been fabricated by a photo-alignment method using poly (vinyl cinnamate), and the effect of the azimuthal anchoring energy on the electrooptical performance has been studied theoretically and experimentally. The results show a large reduction in the driving voltage of IPS samples with decreasing azimuthal anchoring energy, which demonstrates the usefulness of the photo-alignment method for fabricating IPS-LCDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…These materials exhibit unique properties that enable them to be used for a variety of applications, including displays [1][2][3], telecommunication switching [4,5], and optical storage [6,7]. In particular, due to the increasing market for high definition displays, liquid crystal displays (LCDs) have become a prominent area of research in the LC field, as they hold the potential for enabling displays with higher resolution, lighter weight, and reduced thickness.…”
Section: Introductionmentioning
confidence: 99%
“…These materials exhibit unique properties that enable them to be used for a variety of applications, including displays [1][2][3], telecommunication switching [4,5], and optical storage [6,7]. In particular, due to the increasing market for high definition displays, liquid crystal displays (LCDs) have become a prominent area of research in the LC field, as they hold the potential for enabling displays with higher resolution, lighter weight, and reduced thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Note that V th is independent of cell thickness. From table 3, the experimental V th values of the NLC/B1, NLC/B2, NSLC/1 and NSLC/2 mixtures were all smaller than the theoretical V th of 2.22 V, suggesting fast driving in LC devices [96][97][98][99][100]. Moreover, figures 8(a)-(e) show that all the LC mixtures retained excellent bright-state displays after the application of V sat .…”
Section: Electrooptical Studies Of Lc Mixturesmentioning
confidence: 86%
“…Comparison of the theoretical and experimentally measured values of the LC (Table 4) revealed that the LC mixture system used in this study lowered the V th of the LC (Equation (5)). After the LC cell had undergone photo-alignment, the weaker anchoring energy or larger pre-tilt angle of the alignment film surface could effectively reduce the V th and achieve rapidly driven display effects [126,[184][185][186][187]. In addition, we surmised from Equation (5) that the K eff of the LC itself increased with the incorporation of the acrylic monomer.…”
Section: Electro-optical Properties Of the Nlc2 Systemmentioning
confidence: 98%
“…Since the anchoring energy of the alignment film surface formed after UV light irradiation was weaker [126,183,184], the time required for vertical rotation of the LC molecules was shorter. Therefore, the T r measured for each group of LC cells was around 8-9 ms.…”
Section: Electro-optical Properties Of the Nlc2 Systemmentioning
confidence: 99%